Metadiscourse in informed consent : reflections for improving writing and translation - Garcia-Izquierdo, Isabel (Penerbit Universiti Kebangsaan Malaysia, 2022)
Metadiscourse has been one of the most prolific areas of research in the field of applied linguistics in recent years. It is understood as the way we use language to connect with our audience, which is the result of integrating propositional content and interpersonal factors (Hyland, 2017). In this paper we will analyse Metadiscourse in one of the most complex medical-legal genres: informed consent (IC). Drawing on a small comparable bilingual corpus of texts belonging to this genre for surgery in Spanish and English, the paper aims to analyse (by using Sketch Engine tools) how metadiscursive elements are evident in written IC documents, and to reflect on what aspects need to be taken into account in order to improve the way these documents are written and translated in the future. The Key findings are a low frequency of Interactive resources and a more significant presence of Interactional resources in both corpora. However, boosters are almost non-existent, because a large part of the texts belonging to this genre incorporate pre-established formulaic text. Most of the content is related to the procedures requiring consent and their possible consequences, so the sender almost always tends to avoid universal statements and to display a certain reserve in case predictions are not fulfilled. The conclusion is threefold: some metadiscursive elements in the IC manifest themselves in a different way from other medical genres; a more frequent use of some of the interactive and interactional resources could lead to a better understanding; and finally, it would be important to include the analysis of these metadiscursive elements in the training of future medical writers and translators.